OP0120 The incidence of rheumatoid arthritis and the impact of smoking. (23rd January 2014) - Svendsen, A.J.; Hjelmborg, J.V.; Skytthe, A.; Houen, G.; Kyvik, K.; Junker, P.
Abstract : Background: Incidence figures for rheumatoid arthritis (RA) differ considerably, probably reflecting true variation as well as differences in case definition (+/– classification criteria), severity, case validation, recruitment methods, time periods and ascertainment probabilities. Smoking is the hitherto strongest environmental risk factor for RA but has only been evaluated in case control studies. Objectives: To measure the incidence of rheumatoid arthritis in a cohort of Danish twins in order to validate the external validity of twin studies with respect to RA and to determine the impact of smoking on RA occurrence in a cohort study. Methods: Through postal surveys we have recruited RA cases from nation-wide twin birth cohorts and validated the diagnosis through clinical examination, medical records, serology. Completeness was estimated through record linkage with the Danish National Patient Registry and the Danish Register of Causes of Death. Information on smoking was obtained by successive self-administered questionnaires and in-person interviews of Danish twins from 1966 through 2002. Only smoking before RA was diagnosed was classified as "ever smoking''. Results: A total of 56, 707 individual twins were enrolled of which 45, 280 responded, yielding a response rate at 80%. After validation162 twins fulfilled the RA criteria, IgM-RF+ 81% (95%CI: 75 to 87), ACPA+ 77% (95%CI: 71 to 84), shared epitope+ 77% (95%CI: 71 to 84) and nodular disease+ 47% (95%CI: 39 to 55). The point prevalence was 0.20% (95%CI 0.14% – 0.27%) in men, 0.54% (95% CI: 0.44% – 0.64%) in women and 0.37% (95% CI 0.31% – 0.43%) in men and women, age- and sex adjusted to the 2004 Danish population. The age adjusted annual incidence per 100.000 person-years was 13.3 (95%CI: 9.6 to 18.1) in men, 27.3 (95%CI: 22.6 to 32.6) in women and age and sex adjusted 20.0 (95% CI: 17.0 to 23.3) in both sexes. Missing information on smoking was 9% and 12% among RA cases and the population at risk respectively. The incidence rate ratio of ever smoking was 2.0 (95% CI: 1.4 to 2.9). Conclusions: The incidence of RA with age at onset after 55 years was lower than reported in other Scandinavian register based studies of singletons. However, the incidence corresponded to previous figures on RA patients with clinically important loss of physical function, indicating that disease severity differed between the studies. Preclinical smoking doubled the risk of acquiring RA, in particular RA with late age at onset. References: [1] Uhlig T, Kvien TK, Glennas A, Smedstad LM, Forre O. The incidence and severity of rheumatoid arthritis, results from a county register in Oslo, Norway. JRheumatol. 1998;25(6):1078-84. [2] Pedersen JK, Svendsen AJ, Horslev-Petersen K. Incidence of Rheumatoid Arthritis in the Southern part of Denmark from 1995 to 2001. OpenRheumatolJ. 2007;1:18-23. [3] Englund M, Joud A, Geborek P, Felson DT, Jacobsson LT, Petersson IF. Prevalence and incidence of rheumatoid arthritis in southern Sweden 2008 and their relation to prescribed biologics. Rheumatology (Oxford). 2010 Aug;49(8):1563-9. Disclosure of Interest: None Declared